The Influence Of Celebrity Endorsement On Repurchase Intention With The Role Of Brand Image, Brand Credibility, And Brand Trust As Mediation On The Somethinc Brand - Windy Christalia; Maya Ariyanti; Dedi Iskamto (Al-Makki Publisher, 2025)
The beauty industry in Indonesia is increasingly competitive with local brands such as Somethinc using celebrity endorsements as a marketing strategy. This study analyzes the influence of celebrity endorsement (attractiveness, trustworthiness, and expertise) on repurchase intention with brand image, brand credibility, and brand trust as mediation variables. The research method used a quantitative approach with 397 respondents analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The results of the study show that celebrity endorsements have a significant effect on brand image, brand credibility, and brand trust. Brand image and brand credibility have been shown to have a positive effect on repurchase intention, while brand trust does not show a significant influence. In mediation analysis, brand image mediates the relationship between trustworthiness and expertise and repurchase intention, while brand credibility mediates the relationship between attractiveness and expertise and repurchase intention. However, brand trust does not significantly mediate the relationship between celebrity endorsement and repurchase intention. This research provides practical implications that companies need to select endorsers based on trust and expertise, as well as build a strong brand image and credibility to increase consumer loyalty.